PENGARUH LABA KREDIT DAN NON PERFORMING LOAN TERHADAP RETURN ON ASSETS (Studi Empiris Pada Perusahaan Pembiayaan Yang Terdaftar Di Bursa Efek Indonesia) - MUHAMMAD RAHARDYAN; Dion Yanuarmawan (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2014)
The purpose of this study was to examine effect of credit profit and non performing loans on profitability as measured by return on assets. Research object is a Registered Finance Company in Indonesia Stock Exchange from 2008 - 2012 This study used a descriptive quantitative method that consists of three variables: Income Loans and Non-Performing Loans as independent variables and ROA as the dependent variable. The type of data used is quantitative data and data sources used are secondary data. This data collection technique is the technique of documentation and literature study. Methods of data analysis used in this study is multiple regression analysis and tested by t-test.The test results showed that the levels of credit has a significant effect on profitability. These results can be seen in the R Square of 0.522, which means the relationship between the profitability of credit has a very strong relationship. The results of this study confirmed the hypothesis testing results through the t test showed a significance level of 0.000 and credit profit 0,046 NPL, both are below 0.05, which means the level of income and credit NPL significant effect on profitability (ROA).